2017
DOI: 10.1007/s00107-017-1266-8
|View full text |Cite
|
Sign up to set email alerts
|

Properties of particleboard produced from post-industrial UF- and PF-bonded plywood

Abstract: An approach based on the recycling of waste plywood as a recovered wood resource for the particleboard industry is described. It is demonstrated that post-industrial urea-(UF) and phenol-formaldehyde (PF) bonded plywood can be effectively shredded to the form of the recovered particles that can be a valuable material in particleboard manufacturing. The effects of shredding conditions and binder type on the recovered particles characteristics and the mechanical properties of the particleboards were analyzed. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…However, the PBs containing the recyclate from the plywood showed worse moisture properties (TS-2h, 9.42%; TS-24h, 26.71%; WA-2h, 37.68%; WA-24h, 79.40%) than the control PB. Laskowska and Mamiński [36] mentioned that in the case of the recyclates from plywood bonded with UF and PF resin added to the core layer of PBs, the thickness swelling (TS-24h, 8 to 10%) in the boards manufactured from recycled plywood bonded only with UF resin was similar to the swelling in the control PB from wood particles. On the other hand, the thickness swelling of the PBs manufactured based on a waste mixture-i.e., from recycled plywood bonded with PF resin or UF resin and with the recyclate proportions of 25, 50, 75 and 100 wt.%-was 25 to 200% higher compared to the control PB bonded with UF resin.…”
Section: Property Of Pbmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the PBs containing the recyclate from the plywood showed worse moisture properties (TS-2h, 9.42%; TS-24h, 26.71%; WA-2h, 37.68%; WA-24h, 79.40%) than the control PB. Laskowska and Mamiński [36] mentioned that in the case of the recyclates from plywood bonded with UF and PF resin added to the core layer of PBs, the thickness swelling (TS-24h, 8 to 10%) in the boards manufactured from recycled plywood bonded only with UF resin was similar to the swelling in the control PB from wood particles. On the other hand, the thickness swelling of the PBs manufactured based on a waste mixture-i.e., from recycled plywood bonded with PF resin or UF resin and with the recyclate proportions of 25, 50, 75 and 100 wt.%-was 25 to 200% higher compared to the control PB bonded with UF resin.…”
Section: Property Of Pbmentioning
confidence: 93%
“…Laskowska and Mamiński [36] mentioned that recycled particles from plywood added to the core layer of PBs resulted in a decrease in the MOR by 13 to 91% compared to the control PB. Such a significant decrease in bending strength could be due to the less-narrow shape of wood particles from plywood and their larger area.…”
Section: Property Of Pbmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, Yang (2007) [11] studied the use of recycled wood-waste chips for the production of particleboards for use in kitchens, bathrooms, as a flooring material, and in outdoor equipment. Moreover, Laskowska & Mamiński in 2018 showed that it is possible to substitute 20-100% of virgin material with post-industrial plywood [12]. In another work, the addition of 30-50% of recovered MDF into PB production was proven possible but with adverse influences on the mechanical and physical properties of the final products [13].…”
Section: Introductionmentioning
confidence: 99%
“…The surface of the cacao pod particleboard was very rough indicating that the bonding between the particles and the adhesive was poor. This could be as a result of high bulk density and low aspect ratio of the biomass material [37] [38].…”
Section: Scanning Electron Microscope (Sem) Analysis Of the Manufactumentioning
confidence: 99%